Fatty Acid Profiling in Facial Sebum and Erythrocytes From Adult Patients With Moderate Acne - Cao, Ke; Liu, Ye; Liang, Ningning; Shen, Xia; Li, Rui; Yin, Huiyong; Xiang, Leihong (Frontiers in Physiology, 2022)
Fatty acid (FA) metabolism has been involved in acne vulgaris, a common inflammatory skin disease frequently observed in adolescents and adults, but it remains poorly defined whether distributions or location of FA in facial sebum as well as those in the circulation differentially correlate with the disease. In a cohort of 47 moderate acne patients and 40 controls, sebum samples from forehead and chin areas were collected using Sebutape adhesive patches and erythrocytes were separated from the fasting blood. Total FAs were analyzed by gas chromatograph-mass spectrometry method. Compared to control female subjects, female patients showed increased levels of saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA) from both facial areas, whereas decreased levels of polyunsaturated fatty acids (PUFA) from chin areas were observed. Interestingly, the levels of docosahexaenoic acid (DHA) in the circulating erythrocytes were significantly decreased in male patients compared with control. In addition, DHA levels in erythrocytes were positively correlated with PUFA from sebum only in male subjects. Furthermore, female patients with moderate acne had more severe sebum abnormity and chin-specific FA profiles, consistent with higher acne incidences than male in adulthood, especially in the chin areas. Importantly, serum insulin-like growth factor 1 (IGF-1) levels were positively correlated with SFA and MUFA from sebum only in male subjects. In summary, differential spatial FA distributions in facial sebum and correlation with those in erythrocytes and IGF1 levels in serum may shed some light into the pathology of acne in male and female adults.